Factors affecting the utilization of public health care services among households in Lahore district, Pakistan - Arshad, Junaid (2019)
The contemporary research literature, in the case of the public health care system in Pakistan, has continuously reported that the public health care services offered to the citizens of the country are underutilized. However, many factors motivate or trigger the utilization of public health care services among the citizens. A public health care unit is an integral part of a social and medical organization, the function of which is to provide for the population complete health care curative and preventive. Increasing awareness of the general public regarding healthcare issues, public expectations from healthcare providers, availability of multiple healthcare resources to some people and increasing costs of treatment all have a definite bearing on the utilization of health care services from public healthcare units. There are various problems faced in utilization of public health care services like availability of equipment’s, overcrowding, delay response in emergency, cleanliness and lack of proper guidance that creates a lot of problems for the patients and for this purpose following study was aimed to determine the factors affecting the utilization of Public healthcare services among the household of the Lahore District.